Indeks Kesesuaian Wisata di Pantai Pasir Putih, Kabupaten Karangasem - Subandi, I Komang; Dirgayusa, I Gusti Ngurah Putra; As-syakur, Abd. Rahman (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018), 2017)
The study of tourist suitability index (IKW) was conducted in Pasir Putih Beach, Bugbug Village, Karangasem Sub-district, Karangasem district.  Data was collected for 1 (one) month in January 2017 at 4 observation stations. Sources of primary data are obtained from observations and interviews with tourists and secondary data obtained from literature that related to agencies in Pasir Putih beach. Purposive sampling is used as a method for data collection. The data collected are incluted: coastal type, beach width, water depth, coastal slope, water base material, water flow velocity, waters brightness, coastal closure, harmful biota, and freshwater availability. The analysis of IKW for recreation beach category refers to the matrix of tourism and tourism conformity classification. The limiting factor of IKW in Pasir Putih Beach is coastal land cover and wide beach. IKW value for tourism activities in the beach recreation category at Pasir Putih Beach at station I of 94.23%, II of 96.79%, III by 85.89%, and VI of 81.41%. All stations are categorized as suitable (SS) for coastal tourism activities. Zone utilization coastal tourist area for swimming and sunbathing done at station I and II. Zone utilization area for recreation of a walk are station I, II, III, and IV. Station IV at south area including zone of sacred area.